Development of Significant Learning through Scratch Programming Logic of Secondary School Students - Gomez Zermeño, Marcela Georgina; Blanco Mejía, Dayane (The international journal of technologies in learning, 2020)
This research finds out how the implementation of educational software “Scratch” would enhance the meaningful learning of programming logic in secondary school. We worked on a quantitative approach and quasi-experimental design research, which allowed us to work with an experimental and a control group. The study was conducted at an educational institution located in the city of Aguachica Cesar, Colombia, with ninth-grade students, supported by teachers and Information and Communications Technologies. The instruments used were the non-participant observation, and a pre-test and post-test, which allowed researchers to determine the potential of the Scratch educational software for meaningful learning through the development of activities that facilitated the appropriation and strengthening of programming concepts. The relevance of motivation and methodological strategy implemented by the teacher during class generated dynamic contexts to promote meaningful learning.